Tantri’s Anxieties and Her Defense Mechanism in The Film Sekala Niskala (2018) - Natania Marcella; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2024)
This thesis discusses the anxieties and defense mechanisms in Tantri, the protagonist of Indonesian indie film Sekala Niskala (2018). This pivotal film of Kamila Andini tells the story of Tantri, a Balinese girl, dealing with her twin brother, Tantra’s terminal illness. In this study, we are investigating Tantri’s anxieties and her ego’s defense mechanisms according to Sigmund Freud’s anxiety theory and his and Anna Freud’s defense mechanism theory. We found that Tantri displayed reality, neurotic, and moral anxiety. Her reality anxiety of Tantra’s deteriorating health extended to her neurotic anxiety and moral anxiety. As a response, Tantri’s ego applied the defense mechanisms of repression and sublimation. Tantri’s repression was manifested in a pretense of reality and dreams that revealed the fears and desires; her sublimation was expressed through a dance. The results of this study show that anxiety and defense mechanisms are universal in different stages of life and all social backgrounds.